Upaya Penanaman, Pemanfaatan Serta Pembuatan Jamu Godok Dari Tanaman Obat Sambiloto Dimasa Pandemi Covid-19 Di Desa Palir Kecamatan Tengahtani Kabupaten Cirebon - Yayan Rizikiyan; Sulistiorini Indriaty; Deni Firmansyah; Inayatul Fajriyah (Jurnal Abdi Masyarakat Kita, 2022)
The Covid-19 that has hit the world has encouraged people to boost their immune systems. STF Muhammadiyah through Community Service (PkM) activities with community members, village officials in Palir Village, Tengahtani District, Cirebon Regency are directly involved in conducting outreach activities, planting, utilizing, and making herbal medicine from the bitter godok plant. The activity was carried out at the Palir village hall with 36 socialization participants. Before and after the socialization activities, residents filled out questionnaires on how to plant and use bitter plants. This activity was carried out using the presentation method, playing videos on how to make simplicia and making herbal medicine, question and answer discussions, pasting and distributing brochures at residents' homes and the meeting hall, and distributing bitter plant seeds to the community. The community did not know how to plant and use bitter plants before the PKM activities were carried out but after the socialization activities, there was an increase in the percentage of residents' knowledge about planting and using bitter plants. Score 3 there was a significant increase before and after PKM activities, from 11.11% to 56.48%. So that with this PKM activity, the community will increase their awareness and knowledge about the benefits, how to plant, processing bitter to improve the level of public health.